Rancang Bangun Sistem Informasi Pengarsipan di PLN Rayon Rancaekek - An-Nisa Aina Nuwaid; Encep Supriatna; Elsa Fauziah (Jurnal Dimamu, 2022)
In today's era, information systems are an important factor in a company, one of which is in the field of archiving. Archiving at the State Electricity Company (SEC) Rayon Rancaekek still uses a semi-computerized method, which raises several problems, namely difficulty in finding data, not yet integrated transaction files with reports so that reports cannot be generated automatically, the length of the data calculation process because it is still done manually, there is a risk of data being double input and deleted, as well as lost or damaged documents. The purpose of this final project is to simplify data retrieval, integrate transaction files with reports so that reports can be presented after the transaction process, streamline the calculation of archived data, avoid double input and deleted data, and anticipate lost or damaged documents. The research and system development method used is the System Development Life Cycle (SDLC) with the Waterfall model. This system is made using Microsoft Visual FoxPro 9.0 and FoxPro database. System analysis and design tools used in this final project are Flow map, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), database relation schema, and Structure Chart. With the system design made, it can be concluded that the search for archive data becomes easier, all files are integrated so that reports can be presented at any time, the data calculation process can be carried out more effectively, double input data and the risk of data loss can be anticipated, as well as loss and damage data can be anticipated.